Peningkatan Kemampuan Numerasi Siswa Sekolah Dasar melalui Pelatihan Matematika Kontekstual di Desa Marendal - Tsuwaibatul Aslamiyah Lubis (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This community service aims to improve the numeracy skills of elementary school students in Marendal Village through contextual mathematics-based training. The methods used in this program are lectures, discussions, and practice questions based on everyday problems. The evaluation results show an increase in students' understanding of basic mathematical concepts and an increase in their learning motivation. This activity is expected to be a model for numeracy literacy improvement programs in other areas.